2022
DOI: 10.3389/fpsyg.2022.824543
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing and Externalizing Symptoms in Adolescents With and Without Experiences of Physical Parental Violence, a Latent Profile Analysis on Violence Resilience

Abstract: Questionnaire data from a cross-sectional study on social resilience in adolescence, with a sample of N = 1,974 Swiss seventh grade high school students ages 12–14 (M = 11.76; SD = 0.65) was used to identify and compare violence resilience profiles. Person-centered latent profile analysis (LPA) was applied and allowed for the grouping of adolescents into profiles of internalizing (depression/anxiety, dissociation) and externalizing symptoms (peer aggression, peer victimization, classroom disruption) and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 101 publications
(194 reference statements)
2
21
0
Order By: Relevance
“…CM has also been shown to increase lifetime psychopathology as evidenced by neural responses to threatening faces and LPP signaling (Sandre et al, 2018). Interestingly, CM is also more strongly associated with the development of later internalizing and externalizing symptoms, whereas ETV is more associated with externalizing symptoms only (Estrada et al, 2021, Aksoy et al, 2022. Currently, we know that children and adolescents typically show more symptoms of anxiety and anger, less verbalization of hopelessness, and less negative symptoms in comparison to adults' populations who have depression (Luyten & Fonagy, 2018).…”
Section: Key Differences In Youth and Adolescent Psychopathologymentioning
confidence: 99%
See 2 more Smart Citations
“…CM has also been shown to increase lifetime psychopathology as evidenced by neural responses to threatening faces and LPP signaling (Sandre et al, 2018). Interestingly, CM is also more strongly associated with the development of later internalizing and externalizing symptoms, whereas ETV is more associated with externalizing symptoms only (Estrada et al, 2021, Aksoy et al, 2022. Currently, we know that children and adolescents typically show more symptoms of anxiety and anger, less verbalization of hopelessness, and less negative symptoms in comparison to adults' populations who have depression (Luyten & Fonagy, 2018).…”
Section: Key Differences In Youth and Adolescent Psychopathologymentioning
confidence: 99%
“…Additionally, youth with less language skills may also not benefit as much with talk therapy as adolescents (Blom et al, 2014). Older youth tend to be more capable to grasp onto core CBT concepts compared to younger youth, but usually have more life-related difficulties, more internalizing problems, have more psychosocial challenges than youth, and may be less willing to comply with the therapeutic process (Blom et al, 2014, Aksoy et al, 2022. Although many studies have shown that age is not related to treatment completion or outcomes, there are recent studies that demonstrate otherwise (Blom et al, 2014).…”
Section: Key Differences In Youth and Adolescent Psychopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of individual characteristics, analyses of IPV exposure and resilience outcomes have yielded evidence that maternal education level predicted resilience profiles, although gender and ethnicity did not always show significant results [66]. Kassis et al [10] found that only female gender predicted one's assignment to the resilient group versus the non-resilient group in two waves, and migration background (In Switzerland, due to migration policy and the cultural context [67], people with a migration background are either foreign nationals or naturalized citizens according to the Federal Statistical Office [68]. Individuals born in Switzerland whose parents were born in Switzerland and individuals with birth citizenship whose parents were born abroad are excluded.)…”
Section: Protective and Sociodemographic Factors As Predictorsmentioning
confidence: 99%
“…Additionally, Hildebrand and colleagues reported more internalizing and externalizing problems in children and adolescents with lower levels of resilience [ 45 ]. Similarly, Aksoy and colleagues pointed out that adolescents exposed to parental violence exhibited lower internalization symptoms through resilience [ 46 ], while other studies showed that family-related resilience had a significant impact on preventing the development of internalizing problems [ 47 , 48 ]. Previous researchers have examined the mediating effect of resilience on internalizing and externalizing problems, and various other factors.…”
Section: Introductionmentioning
confidence: 99%